On Thermal Conditions of Culverts in Cold Regions - Tommik, Karina (Luleå tekniska universitet, Geoteknologi, 2024)
Culverts play a crucial role in road and railway construction projects by facilitating drainage in embankments. However, in cold climates with seasonally frozen ground, frost-related damages around culverts are a common challenge. Culverts alter the thermal conditions of the surrounding embankment by allowing cold air to flow through the structure, leading to deeper frost penetration compared to adjacent areas. Accurately estimating the depth of frost penetration and the resulting heave is challenging due to the complex thermal dynamics within culverts, influenced by factors such as air temperature, wind, solar radiation, construction materials, and the dimensions of both the culvert and the embankment. To better understand these thermal conditions, a field investigation was conducted near Luleå, Northern Sweden, monitoring three culverts with varying dimensions (diameter/length: 0.6/20 m, 0.8/17 m, and 3.4/30 m) from October 2020 to June 2021. Data on temperatures and air velocities inside the culverts, along with outside air temperatures, were collected and analysed. The study revealed that both snow cover and wind significantly influence temperature distribution within the culverts. During the early freezing period, when snow cover is insufficient to block the ends of the culverts, airflow through the culvert causes internal temperatures to closely follow external air temperatures, with higher airflow velocities resulting in a greater correlation. Conversely, when the culverts become obstructed by snow, internal temperatures stabilize and are less influenced by external conditions. A second field investigation from January to April 2023 focused on measuring soil temperatures around a fourth culvert (0.6 m diameter, 22 m length) to determine frost depth. The temperatures 0.6 m from the centre of the culvert are measured from 0.1 to 2.5 m depth from the pavement surface. Control measurements are carried out in a nearby road section without the culvert. The results indicated that presence of a culvert that is ...